Estado e proteção social na era desenvolvimentista brasileira - Santos Filho, Eurílio Pereira (2000)
This thesis, from both keynesian and post-keynesian perspectives, seeks to apprehend the structural and irreplaceable role played by the public sector financing for the success of na "effective demand economy". Secondly, by assuming the conception according to which in peripheral capitalist states development policy is represented by a course of action taken by thoses states as a means of increasing its capacity as a regulating entity, this work tries to retain those most caracteristics elements of the brazilian development project in order to specify the public financing pattern devoted to the social protection system engendered by such na economic development model. Also pointed out is t~at the military govemments, between 1964-1980, conceived and executed a social protection system different from that previously applied in Brazil, regarding its complexity and claims of universality. However, one should notice that,' in comparison with that social protection system followed by developed countries - consolidated through the "glorious thirties", whose main element was the notion of universal and equalitarian citizenship - the one adopted by the brazilian state may be considered as a real simulacrum.